PENGGUNAAN MEDIA SOSIAL DAN IMPLIKASINYA TERHADAP DINAMIKA PSIKOLOGIS INDIVIDU: SEBUAH TINJAUAN LITERATUR SISTEMATIS BERBASIS PENDEKATAN TEORITIK - Uswatun Mukharomah; Angelita Indah Kamelia; Ahmad Khairul Fasya (PT. Hasba Edukasi Mandiri, 2026)
The rapid development of social media over the past two decades has fundamentally changed the way humans interact, shape identity, and perceive themselves. This literature study aims to identify, analyze, and synthesize findings from various studies regarding the impact of social media use on individuals' psychological health, integrating them into an established psychological theory framework. The method used was a systematic review of 45 scientific articles published between 2015 and 2025. The results of the study indicate that the impact of social media on individual psychology can be understood through three main frameworks: Festinger's Social Comparison Theory, Bandura's Social Cognitive Theory, and Deci and Ryan's Self-Determination Theory A significant relationship has consistently been found between excessive social media use and increased symptoms of depression, social anxiety, and sleep disorders, especially among adolescents and young adults. The implications of this study include the need for psychology-based digital literacy as well as more ethical and human-centered platform design.